The Strength of Ibn Rushd’s Integration of Religion and Philosophy: An Islamic Historical Discourse - Soleh, Achmad Khudori; Rahmawati, Erik Sabti (Journal of Al-Tamaddun, 2023)
Ibn Rushd’s thoughts on the integration of religion and philosophy exerted a major influence on Medieval Jewish, Christian and Islamic philosophy. However, a study that writes the full concept of Ibn Rushd’s integration and its advantages has yet to be found. This study aims to thoroughly analyze Ibn Rushd’s concept of the integration of religion and philosophy, discover the strengths of the integration, and identify its logical consequences. This study uses the content analysis method with primary sources as the main data. The results of the study indicate that (1) Ibn Rushd integrates religion and philosophy by combining three things from religion and philosophy: sources, methods, and goals. (2) The strength of Ibn Rushd’s integration lies in the integrity of the aspects involved, the placement of ratios at a very high position, the principle that philosophical thinking is part of religious order, and the use of allegorical interpretation (ta’wil) of the holy verses. The implication shows that religion and philosophy become inseparable, and the movement for integration must be a movement towards each other, between religion and philosophy. Ibn Rushd’s thoughts on integration can be the basis of the efforts to integrate contemporary religion and science.